Harnessing hydrogen sulfide in injectable hydrogels that guide the immune response and osteoclastogenesis balance for osteoporosis treatment - Lianghua Jiang; Yubin Wu; Zonghan Xu; Mingzhuang Hou; Shayang Chen; Chao Cheng; Dan Hu; Daming Lu; Xuesong Zhu; Chong Li (Materials Today Bio)
Elevated levels of oxidative stress, inflammation, and a dysregulated osteoclastogenesis balance frequently characterize the microenvironment of osteoporosis, which impedes the processes of healing and repair. Existing treatment approaches are limited in scope and rely primarily on factors and drugs. An injectable hydrogel designed for the ROS-responsive release of H2S gas is presented in this study. The first network of the hydrogel comprises sodium alginate (SA-SATO) chelated with S-aroylthiooxime (SATO) and an H2S-generating group, while the second network is composed of photocrosslinkable PEGDA. Through the integration of Cys-releasing microspheres that are reactive with ROS, a composite hydrogel was developed that exhibited advantageous mechanical characteristics and biosafety. The composite hydrogel effectively promoted osteogenic differentiation of mesenchymal stem cells, modulated macrophage polarization, decreased inflammatory responses, and halted cell apoptosis, as evidenced by in vitro experiments. Additionally, it released H2S gas and mitigated excess ROS in cells. The efficacy of the composite hydrogel in promoting bone defect repair and regeneration in an osteoporotic model was further validated by in vivo findings. In summary, the composite hydrogel exhibits potential as a viable approach to address osteoporotic bone defects by harmonizing osteogenesis and osteoclast activity, modulating the microenvironment of bone injuries, and reducing inflammation. Consequently, it presents a viable strategy for the efficient repair of bone defects.